Improving field success of biocrust rehabilitation materials: hardening the organisms or softening the environment?. (19th July 2019) - Bowker, Matthew A.; Antoninka, Anita J.; Chuckran, Peter F.
Abstract : Drylands are a widely degraded biome characterized by low productivity and high abiotic stress. Biological soil crust (biocrust) inoculants hold promise as a rehabilitation material in drylands, useful for boosting ecosystem functions including stabilization of eroding soil surfaces. However, biocrust materials cultivated ex situ by humans inconsistently establish under field conditions. We tested two approaches aimed at improving field establishment of biocrust inoculum: exposing the organisms within the inoculum to abiotic stress in an attempt to harden them, and applying habitat ameliorations intended to reduce the stressfulness of the environment. We hypothesized that both approaches in concert would lead to the most consistent field establishment of biocrusts. Overall, addition of biocrust inoculum did enhance biocrust establishment over the 1.5‐year duration of the study but did not result in full recovery. Generally, hardened biocrust inoculum performed no better than inoculum that was not hardened, although one indicator (chlorophyll a ) was enhanced by addition of hardened inoculum in some circumstances. Temporary irrigation was initially an effective habitat amelioration but had no effect on biocrust establishment by 1.5 years. In contrast, application of jute net to the soil surface promoted biocrust establishment both in synergy with and in the absence of inoculum addition. We hypothesize that jute net stabilizes the soil surface, reduces abiotic stress, and enhances resource availability, overcoming barriers to establishment of biocrusts. Currently, there is broad support for the efficacy of habitat amelioration approaches in biocrust rehabilitation, but effective hardening techniques remain elusive.